2011
DOI: 10.1177/1471301211421070
|View full text |Cite
|
Sign up to set email alerts
|

The co-construction of couplehood in dementia

Abstract: Much research has investigated the impact of dementia on spousal relationships. Most often this is from the point of view of the spouse, but occasionally people with dementia are interviewed independently or in parallel. The current study was novel in its aim to understand ‘couplehood’ as it is co-constructed by the couple when one partner has dementia and employed an innovative design that involved interviewing couples together about their relationship. Using grounded theory methodology, the study identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
160
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(177 citation statements)
references
References 27 publications
10
160
0
1
Order By: Relevance
“…Additionally, for some interviewees with dementia, imposed safety was experienced as limiting and led to concerns around carers' involvement in future decisions. This connects with Molyneaux et al (2011) who found limiting independence could lead to conflict.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, for some interviewees with dementia, imposed safety was experienced as limiting and led to concerns around carers' involvement in future decisions. This connects with Molyneaux et al (2011) who found limiting independence could lead to conflict.…”
Section: Discussionmentioning
confidence: 99%
“…This resonates with the narrative therapy concept of externalising problems to resist their influence (Morgan, 2000). Molyneaux, Butchard, Simpson and Murray (2011) found dementia was externalised from relationships, promoting both personhood and couplehood. Friend (1990) proposed older LG individuals build identities based upon socially constructed meanings.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of the prior marital relationship on the couple's adjustment to dementia has also been identified elsewhere (e.g. Daniels et al, 2007;Davies, 2011;Keady, 1999;Keady & Nolan, 2003;Molyneaux, Butchard, Simpson, & Murray, 2011). Thus, Davies (2011) argued that the couple impacted on dementia rather than dementia impacting on the couple, in the sense that the couple's commitment to the relationship prior to the cognitive changes impacted upon how they coped with the dementia.…”
Section: Couples and Dementiamentioning
confidence: 99%
“…Thus couples might use externalising language when referring to the dementia (Molyneaux et al, 2011) or define it as a problem to be overcome together (Robinson, Clare, & Evans, 2005) or begin to do more things together (Hellstrom & Lunch, 2005;Molyneaux et al, 2011;Robinson et al, 2005). However, although often couples report positive changes from increasingly spending more time together, both members tend to report feeling trapped and wanting more time alone.…”
Section: Couples and Dementiamentioning
confidence: 99%
“…The term 'couplehood' is used to refer to the shared identity and experiences that a couple have that help to reinforce their sense of themselves as a couple. 125 It could be hypothesised that the transition from living together at home to living apart, with one half of the couple in a care setting, may have an impact on couplehood as there may be reduced opportunities for new shared experiences. This could usefully be explored in further research.…”
Section: Recruiting Carersmentioning
confidence: 99%